Can exercise attenuate the negative effects of long COVID syndrome on brain health? - Teo, Wei-Peng; Goodwill, Alicia M. (Frontiers in Immunology, 2022)
The impetus for many governments globally to treat the novel coronavirus (COVID-19) as an endemic warrant more research into the prevention, and management of long COVID symptoms. Whilst the data on long COVID syndrome (LCS) remains scarce, reports suggest a large proportion of recovered individuals will experience ongoing neuropsychological symptoms, even with mild disease severity. The pathophysiology underlying long-Covid is multifaceted, however, evidence suggests that altered inflammatory, neurotrophic, and neurotransmitter pathways within the brain contribute to neuropsychological symptoms reported following COVID-19. Exercise or regular physical activity has long been shown to have positive effects on brain health and cognition through exerting positive effects on inflammatory markers, neurotransmitters, and neurotropic factors analogous to the neurophysiological pathways proposed to be disrupted by COVID-19 infection. Thus, exercise may serve as an important lifestyle factor in the management of LCS. In this opinion article, we present the evidence to support the positive role of exercise in the management of LCS and discuss important considerations and interactions with cardiorespiratory and other complications arising in LCS. We highlight the need for more research and training on the role of sports medicine practitioners and exercise physiologists in the management of LCS and call for further research to understand the optimal dose-responses and exercise prescription guidelines for cognitive benefits and minimising other complications.